Novel cyberspace-oriented access control model - Feng-hua LI; Yan-chao WANG; Li-hua YIN; Rong-na XIE; Jin-bo XIONG (Tongxin xuebao)
A novel cyberspace-oriented access control model was proposed,termed as CoAC,which avoided the threats by comprehensively considering vital factors,such as access requesting entity,general tense,access point,device,networks,resource,internet-based interactive graph and chain of resource transmission.By appropriately adjusting these factors,CoAC emulated most of typical access control models and fulfilled the requirements of new information service patterns and dissemination modes.The administrative model of CoAC was also presented and the functions and methods for administrating CoAC were described by utilizing Z-notation.CoAC is flexible and scalable,it can be further refined and expanded to figure out new opportunities and challenges in the upcoming access control techniques.